Loquat under conversion and biological culture - Calabrese F.; Barone F.; Castello C.; Peri G. (First international symposium on loquat, 2003)
Some of the best Italian loquat cultivars were compared with several foreign varieties in Sicily. They were planted in 1994, kept under conversion (until 1997) and biological culture (since 1998). The best productive cultivars were 'Peluche' (the biggest fruit) and 'Algerie', the earliest to bloom and ripen (March) 'Magdall', 'Bueno', 'El Buenet'. After 7 days from picking, changes in chroma (+), hue and brightness (-), Brix, pH, acids (-), SS-A (+) occurred. 'Russeting' spots caused by wind were worst on 'Peluche', lighter on 'Algerie' fruits. Small 'Mancha morada' (purple spot) spots were found only on some Spanish varieties. Commercial prizes of the biological products were almost twice as much as the ordinary ones (about Euros 2).
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)